Future Face - Easton, Graham (BMJ Publishing Group Ltd., 2004)
An exhibition at the Science Museum, London SW7, from 1 October 2004 until 13 February 2005. Admission free www.sciencemuseum.org.uk/exhibitions/futureface/ Rating: ★★★★